Detection of African swine fever virus antibodies in serum using a pB602L protein-based indirect ELISA - Yang, Yang; Xia, Qiqi; Sun, Qin; Zhang, Yan; Li, Yuhao; Ma, Xiaochun; Guan, Zhixin; Zhang, Junjie; Li, Zongjie; Liu, Ke; Li, Beibei; Shao, Donghua; et al. (Frontiers in Veterinary Science, 2022)
African swine fever (ASF) is an acute, highly contagious, and deadly infectious disease with a huge impact on the pig industry. It is caused by the African swine fever virus (ASFV). The most acute forms of ASF in domestic pigs have mortality rates of up to 100%. The lack of a commercial vaccine and effective therapeutic drugs has brought great challenges to the prevention and control of ASF. At present, the detection volume of African swine fever is huge, so there is a need for more sensitive and accurate detection technology. The protein pB602L, as a late nonstructural protein, has strong antigenicity and a high corresponding antibody titer in infected pigs. In this study, the B602L gene was cloned into the prokaryotic expression vector pCold Ⅰ, and prokaryotic expression of the soluble pB602L protein was induced by IPTG. Western blot analysis showed that it has strong immunogenicity. Using purified recombinant pB602L protein as antigen, an indirect ELISA method for detecting anti-ASFV was established. The detection method showed excellent specificity without cross-reactions with antibodies against PRRSV, CSFV, JEV, and GETV. The method could detect anti-ASFV in serum samples that were diluted up to 6400 times, showing high sensitivity. The coefficients of variation of the intra-assay and inter-assay were both <10%. The assays had excellent specificity, sensitivity, and repeatability. In summary, we developed an accurate, rapid, and economical method for the detection of anti-ASFV in pig serum samples with great potential for ASF monitoring and epidemic control.